Synthesis, Spectral and Antibacterial Studies of New 1-(4-Antipyrine azo)-2-hydroxy-3, 6-Disulphonic Acid Sodium Salt with Group IIB Metal ions - Alyaa Khider Abba (Journal of Global Pharma Technology, 2016)
A series of IIB group metal complexes have been synthesized from new azo ligand derived from 4-amino-antipyrine and 2-hydroxy-3, 6-disulphonic acid sodium salt. The structural features have been done on the basis of metal content C.H.N analysis, molar conductance measurement, FT-IR, UV-Vis and HNMR spectral studies. The natures of the prepared complexes were studied according to the Jobs method and Mole ratio method after fixing the optimum condition of pH and concentration. Beers low obeyed over a concentration range (1×10-4 -3×10-4) M .The stability constant of the complexes and Gibbs free energy have been conformed. The antibacterial studies were also studies.Keywords: azo dye, 4-aminoantipyrine, Spectral studies, Antibacterial studies.